2017
DOI: 10.3892/etm.2017.5362
|View full text |Cite
|
Sign up to set email alerts
|

TBX1 loss‑of‑function mutation contributes to congenital conotruncal defects

Abstract: Abstract. Conotruncal defects (CTDs) account for ~30% of all types of congenital heart disease and contribute to increased morbidity and mortality rates. Increasing evidence suggests that genetic risk factors are involved in the pathogenesis of CTDs. Mutations in a number of genes, including the TBX1 gene that codes for a T-box transcription factor essential for normal cardiovascular development, may contribute to the development of CTD. CTDs are genetically heterogeneous and the genetic defects responsible fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 60 publications
(49 reference statements)
0
14
0
Order By: Relevance
“…Different size of deletions in TBX1 have been reported in patients with VCF/DiGeorge syndrome [ 57 , 58 ]. In addition, TBX1 point mutations have also been linked to non-syndromic CHD in humans, including isolated TOF, VSD, PA, DORV, IAA and aortic arch anomalies [ 59 , 60 , 61 , 62 ]. Moreover, some authors reported that Tbx1 deficiency in mice may cause dosage-dependent anomalies of the cardiac outflow tract [ 63 , 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different size of deletions in TBX1 have been reported in patients with VCF/DiGeorge syndrome [ 57 , 58 ]. In addition, TBX1 point mutations have also been linked to non-syndromic CHD in humans, including isolated TOF, VSD, PA, DORV, IAA and aortic arch anomalies [ 59 , 60 , 61 , 62 ]. Moreover, some authors reported that Tbx1 deficiency in mice may cause dosage-dependent anomalies of the cardiac outflow tract [ 63 , 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…And dysregulation of TBX1 could lead to variant CHDs, including VSD, ASD, PDA, TOF, PA or PS with VSD. In other studies, the TBX1 loss-of-function mutation was found to contribute to congenital conotruncal defects in humans (Xu et al, 2014;Zhang et al, 2018).…”
Section: Figmentioning
confidence: 77%
“…Tbx1 also interacts with Foxa2 and is necessary for its expression in the pharyngeal mesoderm (Hu et al, 2004). Patients with haploinsufficiency for Tbx1 present a spectrum of conotruncal anomalies, including PA (Xu et al, 2011;Zhang et al, 2018).…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations